TINJAUAN YURIDIS TERHADAP WACANA PERUBAHAN MASA JABATAN PRESIDEN MENURUT KETENTUAN PERUNDANG-UNDANGAN - Muhammad Nabil Naufal; Andy Usmina Wijaya (Fakultas Ilmu Sosial dan Humaniora, 2025)
In many countries, including Indonesia, the issue of presidential term limits is significant. In the current context of the constitutional debate, one of the provisions being discussed is the presidential term, which faces opposition from both supporters and opponents of change. The topic of presidential term limits often arises in political and legal discourse in Indonesia. The purpose of changing presidential terms is to provide greater opportunities for successful leaders in governing the country. However, because it can erode fundamental principles of democracy and potentially lead to tyranny, this discourse has also received various criticisms. This research falls under normative research, also known as library research. Therefore, it is crucial to conduct legal analysis of this study, taking into account the constitution and observing the current applicable laws.